(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the system of synonyms in the Uzbek language with a specific focus on their stylistic functions across different communicative contexts. Synonyms in Uzbek not only serve as lexical alternatives but also reflect various stylistic registers—formal, informal, poetic, archaic, and dialectal—thus enhancing the expressive richness of the language. The research adopts a mixed-method approach combining traditional lexicological analysis, stylistic categorization, and corpus-based study using the Uzbek National Corpus. Findings reveal that synonym usage is highly dependent on discourse type, genre, and sociolinguistic variables such as speaker age, region, and formality. The paper classifies synonymic relations into stylistic equivalence, stylistic gradation, and stylistic divergence, providing concrete examples from literary, journalistic, conversational, and academic texts. The study argues for a stylistically aware approach to synonym teaching and recommends the development of a corpus-informed Uzbek synonym dictionary. This work contributes to the fields of Uzbek lexicology, stylistics, and applied linguistics by bridging semantic theory with functional usage in context.